The Media and Ways to Teach Vocabulary for Students with Special Needs - Lailatun Najakh (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
It is known that students with special need have a different treatment in their teaching-learning process although, some of them with certain conditions can be allocated in the regular school. Therefore, the writer seeks the use of visual media in teaching vocabulary to students with special needs at SMKN 13 Malang with focused on the kinds of visual media and the ways of using visual media. This study was conducted on qualitative design to draw data of the topic discussed. It involved an English teacher who used visual media in teaching vocabulary in SMKN 13 Malang, and 12 students with special needs. The instruments to collect the data were observation field note and interview guideline; meanwhile, the methods to collect the data were non-participant observation and semi or partially structured interview. The result showed that the teacher used still pictures, poster, real object, and slides as the kinds of visual media. Also, she used some procedures with the following steps: (1) preparing the media and distributing to them equally or asking them to use it in turn; (2) delivering the rules of using the media; (3) teaching them vocabulary based on material by TPR method with imitating and modeling strategies; (4) giving rewards for their accomplishment during the teaching-learning process; (5) monitoring their understanding by asking them one by one to mention the vocabulary.